1985
DOI: 10.1088/0022-3727/18/9/013
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of chemically sprayed tin oxide and indium tin oxide transparent conductive films

Abstract: Optical and electrical properties of transparent conductive oxide films of undoped and doped SnO2 and In2O3 prepared using the pyrolysis spray method were studied. The optical constants extracted from transmittance and reflectance measurements between 0.25 and 3 mu m are interpreted to give values of the direct allowed band gap (4.54 eV for SnO2:F and 3.80 eV for ITO) and the indirect forbidden band gap (2.77 eV for SnO2 and 2.90 eV for ITO). Typical SnO2:F and ITO films present high transmission ( approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 13 publications
(3 reference statements)
2
9
0
2
Order By: Relevance
“…It is also observed that the refractive index of the SnO 2 films is significantly greater than that the ITO's. A similar behaviour of the n vs λ curves has been reported in the literature for ITO and SnO 2 films deposited by spray pyrolysis [14].…”
Section: From the Interference Fringes Observed In The Transmission Ssupporting
confidence: 85%
See 2 more Smart Citations
“…It is also observed that the refractive index of the SnO 2 films is significantly greater than that the ITO's. A similar behaviour of the n vs λ curves has been reported in the literature for ITO and SnO 2 films deposited by spray pyrolysis [14].…”
Section: From the Interference Fringes Observed In The Transmission Ssupporting
confidence: 85%
“…Phase, structure and lattice constants corresponding to ITO and SnO2 films prepared by spray pyrolysis using the synthesis parameters listed in XRD measurements indicated that the ITO films grow with cubic structure, whereas the SnO2:F films grow with tetragonal structure. In some samples, reflections associated to the Sn 21 Cl 16 (OH) 14 O 6 secondary phase were identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] Hence, the optical band gap for such transitions can be determined by plotting a 2 versus hv and extrapolating the linear portion of the curve to a 2 ¼ 0 as has been done by many groups for various crystalline and amorphous TCOs. [36][37][38][39][40][41][42][43][44] While we note that this formalism is not strictly valid for amorphous materials, modeling the measured optical spectra as a direct allowed transition provided a good fit to the data, much better than for assuming an indirect transition. For this analysis, the absorption coefficient was determined from the measured transmission (T) and reflection (R) spectra using…”
Section: Full Papermentioning
confidence: 99%
“…El óxido de Indio dopado con Estaño más conocido como ITO (Indium Tin Oxide) es un material semiconductor tipo n con una brecha de energía prohibida (E g ) del orden de 3.7 eV, perteneciente al grupo de los materiales denominados TCO (óxidos transparentes-conductores) [3,4]. Se sintetizaron películas delgadas de ITO con propiedades adecuadas para usarlo como contacto eléctrico transparente en celdas solares DSSC.…”
Section: Síntesis Del óXido De Indio Dopado Con Indio (Ito)unclassified